The thing about proof systems like this one is that you never actually want to write proofs in them. Instead, you usually make use of meta-theorems (like the deduction theorem) to make your life easier. I'll describe a proof using the deduction theorem, which could then in principle be unwound (following the inductive proof of the deduction theorem) into a real (but much longer!) proof in the system.
So what's the strategy for proving $(\lnot \beta\to \lnot \alpha)\to (\alpha\to \beta)$? We want to assume $(\lnot \beta\to \lnot \alpha)$ and prove $(\alpha\to \beta)$. To prove $(\alpha\to \beta)$, we want to assume $\alpha$ and prove $\beta$. Ok, how can we prove $\beta$ based on our assumptions $(\lnot \beta\to \lnot \alpha)$ and $\alpha$? Well, rule (4) gives us a limited method of proof by contradiction. If we want to prove $\beta$, it suffices to prove $(\lnot \beta\to \beta)$. And to prove $(\lnot \beta\to \beta)$, we want to assume $\lnot \beta$ and prove $\beta$. Now we're in business: from our assumptions $(\lnot \beta\to \lnot \alpha)$ and $\lnot \beta$, we get $\lnot \alpha$. Together with our assumption $\alpha$, we should be able to use the principle of explosion to get $\beta$. This is implemented by rule (3): we have $(\lnot \alpha\to (\alpha\to \beta)$, so applying modus ponens twice, we get $\beta$.
Let's turn this strategy into a proof:
- $(\lnot\beta\to \lnot \alpha)$ (Assumption)
- $\alpha$ (Assumption)
- $\lnot \beta$ (Assumption)
- $\lnot \alpha$ (MP from 1. and 3.)
- $\lnot \alpha\to (\alpha\to \beta)$ (3)
- $\alpha\to \beta$ (MP from 4. and 5.)
- $\beta$ (MP from 2. and 6.)
- $(\lnot \beta\to \beta)$ (Deduction theorem, discharging Assumption 3.)
- $(\lnot \beta\to \beta)\to \beta$ (4)
- $\beta$ (MP from 8. and 9.)
- $(\alpha\to \beta)$ (Deduction theorem, discharging Assumption 2.)
- $(\lnot\beta\to \lnot\alpha)\to (\alpha\to \beta)$ (Deduction theorem, discharging Assumption 1.)